Efek Berbagai Perlakuan pada Permukaan Metal dan pada Unit Metal Keramik terhadap Ikatan Metal Keramik - Elina Karlina (Journal of Dentistry Indonesia, 2015)
Principally, metal ceramic bonding were determined by availability of forming oxide layer on the interface between metal and ceramic. Only a thin film of oxide layer that needed for provide sufficient adherence. Many investigations were done in order to increase this condition, for example kinds of treatment on the interface e.g. alternative oxidation, sandblasting and finishing metal direction. These investigations purposed to measure the magnitude of metal ceramic bonding through the kinds of test e.g. shear bonding and flexural biaxial testing. Besides, metal ceramic bonding might be detected by the amount of remained ceramic adherence. Treatment on the metal ceramic unit investigated the influence of moisture environment to the metal ceramic bonding.